B vitamins and homocysteine as determinants of bone health: A literature review of human studies - Ilesanmi-Oyelere BL; Kruger MC (John Wiley and Sons Ltd on behalf of British Dietetic Association, 2023)
Although there are several factors related to bone diseases such as physical activity, gender (oestrogen), race/ethnicity, smoking and alcohol habits, nutrition is a modifiable risk factor that could be employed to prevent or manage the onset of bone health diseases such as osteoporosis in humans. Aside from calcium and vitamin D, B vitamins are a group of water-soluble vitamins that play a vital role in cell metabolism. In this review, current evidence on B vitamins and bone health is assessed. Clinical trials (interventions) indicate that treatment with B vitamins impact the concentrations of total plasma/serum homocysteine concentrations (tHcy); however, most studies have reported the lack of an effect of low homocysteine concentrations on bone turnover markers, bone mineral density or fracture risks. Current studies have been inconsistent in their reports on the role of B vitamins and homocysteine in bone health. More data are therefore required to show the mechanism and effect of tHcy and B vitamins on bone mineral density, bone metabolism and fracture risk.
(c) 2022 The Author/s
Keywords: B vitamins; BMD; bone health; bone metabolism; homocysteine; osteoporosis; Humans; Vitamin B Complex; Bone Density; Homocysteine; Osteoporosis; Bone and Bones; Fractures, Bone; Folic Acid; Vitamin B 12